Proceedings of the First International Conference on Combinatorial and Optimization, ICCAP 2021, December 7-8 2021, Chennai, In 2021
DOI: 10.4108/eai.7-12-2021.2314515
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Prototype Fabrication of Manual Cum Automatic Seed Sowing Machine

Abstract: Automatic seed sowing machine are expensive and not affordable by small farmers in India. Traditional method of seed sowing practice causes muscular fatigue. It also leads to severe back ache. This paper focuses on the prototype development of manual cum automatic seed sowing machine at a minimum cost and to reduce the muscular fatigue associated with traditional method of seed sowing practice. The activities of this work include ideation, detail design, analysis and finally prototype development. In the ideat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…In a research of Rajesh and et. al it has been observed that risk based designs on making ergonomical prototype machine for seed sowing may reduce the density of risk from high to moderate and so as lower the tendency for postural hazards (Ramadass, 2021). In another study based upon gender dependent participation it was observed that more that 75% of women are mostly engaged with high risk postures of agriculture relating stooping, squatting, sitting and bending, sometimes erect bending for prolonged period of time leads to postural discomfort and hazards.…”
Section: Posture Analysis Responsible In Wrmsdsmentioning
confidence: 98%
“…In a research of Rajesh and et. al it has been observed that risk based designs on making ergonomical prototype machine for seed sowing may reduce the density of risk from high to moderate and so as lower the tendency for postural hazards (Ramadass, 2021). In another study based upon gender dependent participation it was observed that more that 75% of women are mostly engaged with high risk postures of agriculture relating stooping, squatting, sitting and bending, sometimes erect bending for prolonged period of time leads to postural discomfort and hazards.…”
Section: Posture Analysis Responsible In Wrmsdsmentioning
confidence: 98%